Prevalence of cardiovascular risk factors amongst traders in an urban market in Lagos, Nigeria - T O Odugbemi; A T Onajole; A O Osibogun (Nigerian Postgraduate Medical Journal, 2012)
Aims and Objectives: A descriptive cross-sectional study was carried out to determine the prevalence of cardiovascular risk factors amongst traders in an urban market in Lagos State. Subjects and methods: Tejuosho market, one of the large popular markets was selected from a list of markets that met the inclusion criteria of being major markets dealing in general goods using a simple random sampling technique by balloting. Four hundred (400) traders were selected using a systematic random sampling. Each trader was interviewed with a well-structured questionnaire and had blood pressure and anthropometric measurements (height, weight and body mass index). Results: Female traders made up (74.3%) 297 of the total population. The mean age was 45.48+11.88 and 42.29+10.96 years for males and females respectively. Majority 239 (59.8%) fell within the age range of 35 - 55 years. The cardiovascular risk factors identified and their prevalence rates were hypertension (34.8%), physical inactivity (92%), previously diagnosed diabetes mellitus (0.8%), risky alcohol consumption (1%), cigarette smoking (0.3%) in females and (17.5%) in males, obesity (12.3%) and overweight (39.9%). Conclusion: The study recommended that any health promoting, preventive or intervention programme for this population would have to be worked into their market activities if it is to make an impact.